Development and Design and Heat Treatment of Production, Storage_x000D_ and Mine Drilling Pipes in Petroleum and Geothermal Industries - (:unkn) unknown (My University, 2020)
In this study, sequential and different temperature heat treatments were applied to steels after austenating heattreatment applied to different AISI steel types. The effects of tempering heat treatment applied on the mechanicalproperties of the steel after quenching were investigated. The production of prototypes of the materials to beused in the drilling industry and the improvement of the properties of the drilling pipes used in the geothermal,petroleum, storage and mining sectors by thermal processes determined according to the standards have beenrealized. Different heat treatments have been applied to the materials in AISI standards provided by consideringthe desired material properties of the drill pipes. In order to improve the mechanical properties, the heattreatment process was determined and applied by a wide literature review. The prototypes of the drill rods wereproduced in three different AISI standards (AISI 4130, AISI 4140). Seamless tubes are produced according toAISI 4340 and ductile, semi-ductile and brittle conditions. 946.4 MPa. In addition, corrosion tests showedsignificant corrosion resistance.

Bu çalışmada, farklı AISI çelik türlerine uygulanan östenitleme ısıl işleminden sonra çeliklere sıralı ve farklı_x000D_ sıcaklık ısıl işlemleri uygulanmış. Bu işlemlerden sonra su verme işlemini takiben uygulanan temperleme ısıl_x000D_ işleminin çeliğin mekanik özellikleri üzerine etkileri araştırılmıştır. Sondaj sanayinde kullanılacak malzemelerin_x000D_ protatiplerin üretilmesi, jeotermal, petrol, depolama ve maden sektöründe kullanılan sondaj borularının_x000D_ standartlara göre belirlenen ısıl işlemlerle özelliklerinin iyileştirilmesi gerçekleştirilmiştir. Sondaj borularının_x000D_ istenilen malzeme özellikleri dikkate alınarak temin edilen AISI standartlarındaki malzemelere farklı ısıl işlemler_x000D_ uygulanmıştır. Mekanik özelliklerin iyileştirilmesi için ısıl işlem süreci geniş bir literatür taramasıyla_x000D_ belirlenmiş ve uygulanmıştır. Sondaj çubuklarının protatipleri, üç farklı AISI standardında (AISI 4130, AISI_x000D_ 4140) malzemelerinden 3 er adet olmak üzere protatipler üretilmiştir. Dikişsiz tüpler olarak AISI 4340 ve sünek,_x000D_ yarı sünek ve kırılgan koşullara göre üretilmiştir: Yapılan Isıl işlem deneyleri sonucunda malzemelerin % uzama_x000D_ değerleri %9-18, Max sertlik değerleri 280-495 HB, gerilme değerleri 834,2-1578 MPa ve Minumun akma_x000D_ dayanımı 946,4 MPa ile dikkate değer iyileştirmeler göstermiştir. Ayrıca yapılmış olan korozyon testlerinde_x000D_ kayda değer korozyon direnci göstermiştir.
Petrol ve Jeotermal Sektörü Depolama ve Maden Sondaj Borularının Üretimi, Geliştirilmesi, Tasarımı ve Isıl İşlemi